The Role of Competence and Compensation on Lecturer Performance - Kamesyworo, Kamesyworo; Sriwiyanti (Chakra Brahmanda Lentera Institute, 2023)
Background: Lecturers play a crucial role in the higher education process, supported by various other elements that contribute to the successful implementation of education within the higher education system. The purpose of this study was to find out the effect of competence and Compensation on the performance of lecturers at the Nursing Academy of the Government of Lahat Regency, South Sumatra Province Methods: The design was correlational. The population and sample were all Lecturers of the Lahat Regency Government Nursing Academy, totalling 30 people who were willing to become respondents and research samples. Research variables consist of independent and dependent variables. Independent variables consist of competency and compensation variables, while the dependent variable is Lecturer Performance. Data analysis technique using multiple linear regression analysis to test how much influence the independent variables have on the dependent variable, and the T-test Used to test the significant level of influence of the independent variables on the dependent variable. Results: The results, based on linear regression analysis, obtained a constant value of 1.804, the coefficient value of the Competency variable of 0.470, and Compensation of 0.251, partially that Competence and Compensation have a positive effect on performance. This can be seen from the resulting positive regression equation, which means that if Competence and Compensation are increased, the Lecturer's Performance will increase. The Competency variable has the most dominant influence because the regression coefficient value is the largest, namely 0.470 and followed by the Compensation variable of 0.251. Conclusion: This research has proven that competency and Compensation have a significant effect on lecturer performance, so for further research, it is recommended to examine other variables outside of this variable